PENGEMBANGAN BUDIDAYA IKAN LELE DAN NILA MELALUI PENERAPAN TEKNOLOGI MODIFIKASI PAKAN DENGAN EKSTRAK DAUN KATUK, PEMIJAHAN BUATAN, DAN SEXREVERSAL DI KELURAHAN KARANG HARAPAN KOTA TARAKAN KALIMANTAN UTARA - Diana Maulianawati; Awaludin Awaludin; Meylin Rachmawati (Yayasan Education and Social Center, 2021)
Catfish and tilapia are freshwater fish whose production continues to be increased every year due to high market demand. High market demand encourages cultivators to continue to innovate in accelerating production. Technology must be applied to increase production. Tarakan City produces freshwater fish such as catfish and tilapia. The fish cultivator group (POKDAKAN)